The sociolinguistics of globalization - Blommaert, Jan, 1961-2020 (Cambridge : Cambridge University Press, 2010)
"A Critical Introduction (2005) attempted to sketch these consequences for our understanding of discourse, as well as for our ethos of analysing it. The same approach was applied to literacy in Grassroots Literacy (2008), and I am here bringing the same exercise to the field of sociolinguistics. Each of the books is an attempt, an essai in the classical and original sense of the term, in which I try my best to describe the problem and offer some conceptual and analytical tools for addressing it. And I make this effort because I believe that globalization forces us - whether we like it or not - to an aggiornamento of our theoretical and methodological toolkit"--Provided by publisher.
"Human language has changed in the age of globalization: no longer tied to stable and resident communities, it moves across the globe, and it changes in the process. The world has become a complex 'web' of villages, towns, neighbourhoods and settlements connected by material and symbolic ties in often unpredictable ways. This phenomenon requires us to revise our understanding of linguistic communication. In The Sociolinguistics of Globalization Jan Blommaert constructs a theory of changing language in a changing society, reconsidering locality, repertoires, competence, history and sociolinguistic inequality"--Provided by publisher.
Machine generated contents note: 1. A critical sociolinguistics of globalization; 2. A messy new marketplace; 3. Locality, the periphery and images of the world; 4. Repertoires and competence; 5. Language, globalization, and history; 6. Old and new inequalities; 7. Reflections.
Keywords: Language and languages -- Globalization; Languages in contact; Linguistic change; Sociolinguistics